The anthropomorphic stele at Monte dos Zebros (Idanha-a-Nova): Contextualization amongst other Diadem-Steles in the Iberian Peninsula - Cardoso, João Luís (Complutum, 2011)
This paper describes an anthropomorphic stele found in 1996 at Monte dos Zebros (Idanha-a-Nova, Beira Interior Sul, Portugal). It is a small monolith, incomplete in the lower part and much eroded, particularly on the posterior surface, as a result of exposure to the elements. The monument may be related to a burial mound, probably not of the megalithic type and dating to the Bronze Age, like others in the region. The stele described here has its closest parallel in the stele of Crato, as regards both the shape of the base and the iconography represented. Thus, like that one, it is probably one of the earliest examples in a long continuous series of female steles (indicated by the presence of diadems and “necklaces” and, in a few cases, the female genital organs) produced between the Early Bronze Age and the Late Bronze Age.